Livestock and poultry manure pollution and its future risk forecasting on farmland in Henan Province - WU Rongkang; PAN Fanghui; CHANG Jiayue; ZHANG Xing; TIBAMBA Matthew; WANG Youbao (浙江大学学报. 农业与生命科学版, 2021)
It was analysed comprehensively for farmland pollution by the livestock and poultry manure in Henan Province from 2008 to 2017 and forecasting its future risks, which providing a theoretical basis for Henan Province to arrange rationally the structure of the livestock and poultry breeding industry and carry out the work of pollution control. The study was based on the livestock and poultry breeding data and farmland area data of Henan Province from 2008 to 2017, and analysed the livestock and poultry manure volume, pig dung equivalent, and pollution load of farmland in Henan Province, and made a forecast for the future. The results showed that in the past ten years, the pig dung equivalent emissions, total nitrogen load, total phosphorus load, and pollution risk index of livestock and poultry manure’s farmland load declined. The cities within the highest risk of livestock and poultry manure pollution were Pingdingshan, Hebi, Xuchang and Luohe, and Hebi and Luohe’s livestock and poultry manure pollution risks were the highest in 2017, so the control and treatment of livestock and poultry manure should be strengthened. In the future, the pig population in Henan Province will increase rapidly, and the warning level of Luohe will change from grade Ⅱ to grade Ⅲ in 2025, and the warning levels of Kaifeng and Puyang will change from grade Ⅱ to grade Ⅲ in 2030. So the prevention and control of livestock and poultry manure pollution in Kaifeng, Puyang and Luohe in Henan Province should be strengthened.